Modelling and simulation of optical transmitter for 5G passive optical networks - Sura Adil Abbas; Jaafar A. Aldhaibani (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
5G is altering the communications future. The 5G literature focuses on wireless and radio technology, but fiber optics play a crucial supporting role in signal transmission to and from the next generation of base stations (BSs) that will serve customers. With the increasing bandwidth requirements of 5G ultra-high-speed applications, passive optical networks (PONs) are the optimal solution. Targeting long-reach 5G PONs, an integrated, high-speed, and cost-effective optical transmitter circuit was constructed and tested. This engine can be combined into a 5G-compliant optical transceiver module. For the purpose of validating the engine performance, a theoretical analysis and an OptiSimTM-based design simulation model are carried out. Bit error rate (BER), phase-shifting, and eye diagram were all taken into account when analyzing the transmitter performance. The article findings validate the optical transmitter design. The design is cost-effective and requires no extra components, such as a filter.